THE IMPORTANCE OF AUDITING SERVICES IN THE SECURITY MARKET - Makhmudov Saidjamol , Kadirjanovich (THE INNOVATION ECONOMY, 2025)
The securities market of the Republic of Uzbekistan is a financial mechanism of the economic system in the conditions of economic liberalization, which creates ample opportunities for the circulation of temporarily free funds of the population and economic entities. Because in the conditions of a market economy, highly qualified personnel with an idea of the securities market have developed in economic entities. Secondly, the law on the securities market introduces the concept of disclosure of certain information, which raises the issue of ensuring the use of information by persons who guarantee its discovery and receipt, regardless of the purpose of obtaining information by interested parties in the securities market, and in these conditions, the impartiality and transparency of such information is ensured by audit organizations. Thirdly, some economically large enterprises and organizations, commercial banks have accumulated a large amount of their own funds, which, in turn, creates conditions for participation in the stock market as major investors.